Improved glycemic control in 3, 592 adults with type 2 diabetes mellitus initiating a tubeless insulin management system. (April 2021) - Carlson, Anders L.; Huyett, Lauren M.; Jantz, Jay; Chang, Albert; Vienneau, Todd; Ly, Trang T.
Highlights: There have been few studies of insulin pump therapy in people with T2DM. HbA1c was lower 90 days after initiating Omnipod insulin pump in those with T2DM. Total daily dose of insulin was lower 90 days after initiating Omnipod. The frequency of hypoglycemic episodes was also lower after initiating Omnipod. Abstract: Aims: To compare glycemic outcomes in adults with type 2 diabetes mellitus (T2DM) before and 90 days after initiating Omnipod® or Omnipod DASH® Insulin Management Systems. Methods: In this retrospective observational study (N = 3, 592) change in HbA1c level, total daily dose (TDD) of insulin (n = 3, 053), and frequency of self-reported hypoglycemic events (HE, <70 mg/dL, n = 2, 922) were assessed overall and by prior treatment modality (multiple daily injections (MDI) or continuous subcutaneous insulin infusion (CSII)), age group, and baseline HbA1c category. Results: Change (mean ± SD) in HbA1c was −1.3 ± 1.7% [−14 ± 19 mmol/mol] overall, −1.4 ± 1.7% [−15 ± 19 mmol/mol] for prior MDI users, and −0.9 ± 1.5% [−10 ± 16 mmol/mol] for prior CSII users ( p <0.0001). The percentage of patients with HbA1c ≥9% [≥75 mmol/mol] decreased (49% to 19%), and with HbA1c <7% [<53 mmol/mol] increased (10% to 22%) ( p <0.0001). Prior therapy, age, and baseline HbA1c category were factors affecting change in HbA1c ( p <0.05). Reductions in TDD (overall, −33 ± 52U, p <0.0001) and HE per week (overall, −0.5 ± 2.0, p <0.0001), were seen regardless of prior treatment, age, or baseline HbA1c. Conclusions: Omnipod System use was associated with statistically and clinically meaningful reductions in HbA1c, TDD, and HE compared to prior treatments in T2DM.